Non-aureus Staphylococci Species in the Teat Canal and Milk in Four Commercial Swiss Dairy Herds - Traversari, Julia; van den Borne, Bart H. P.; Dolder, Claudio; Thomann, Andreas; Perreten, Vincent; Bodmer, Michèle (Frontiers in Veterinary Science, 2019)
Non-aureus staphylococci (NAS) are frequently found in milk samples as well as on the teat apex and in the teat canal and are known to be a cause of subclinical mastitis. The objective of this study was to investigate the relationship between NAS species colonizing the teat canal and those causing intramammary infection (IMI) in four commercial dairy herds. Teat canal swabs were obtained and thereafter milk samples were aseptically collected and evaluated for the presence of staphylococci using selective agar plates. Species identification was performed using matrix-assisted laser desorption/ionization time–of–flight mass spectrometry. The relationship between NAS species distribution and sample type (teat canal vs milk samples) was quantified using hierarchical multivariable logistic regression models. The most prevalent NAS species in teat canal swabs were S. xylosus (35%), S. vitulinus (10%), and S. chromogenes (7%), whereas in milk samples S. chromogenes (5%), S. xylosus (5%), and S. haemolyticus (4%) were most prevalent. There were significantly higher odds for S. vitulinus (OR=215), S. xylosus (OR=20), S. sciuri (OR=22), S. equorum (OR=13) and S. succinus (OR=10) to be present in teat canal swabs than in milk samples. Differences between herds in NAS species distribution were found and were most pronounced for S. succinus and a S. warneri-like species. This information aids in the understanding of NAS species as an etiology of IMI and should be taken into account when interpreting milk culture results.